Improving teacher productivity and performance for better learning outcomes in Nigeria public secondary schools (2011)
The paper x-rays school productivity in relation to teachers' productivity in secondary schools. The productivity of teachers in schools has reportedly declined over the years. This assertion is evident from the visible poor performance of students in both internal and external examinations. It specifically assesses the performance of students in two key subjects (English Language and Mathematics) in external examinations held in Nigeria. The paper is of the view that most of the seemingly poor performance of our school System lies on the deficiencies and ineffectiveness of our poorly trained and poorly motivated teachers. The reasons for this apparent low teacher productivity in schools are discussed as well as the challenges and rote of the teacher for improved productivity in the school. It further discusses the factors militating against effective classroom management. The principles and strategies for effective classroom management are also discussed. The paper concludes that a concerted effort is needed to improve the performance of teachers in public schools for the benefit of the entire school System. It identifies an effective classroom management as key to increasing the productivity of teachers and the leaning outcome of students in schools. These include ensuring a hygienic and congenial physical classroom structure; having a good mastery of the subject matter; use of appropriate methods of instruction; and ensuring that teaching and learning is done under organized, planned, and fortified environment with teaching/leaning instructional aides to stimulate students' sense of conception, perception and concentration to -facilitate systematic understanding and acquisition of knowledge in them